Perfluorodecanoic acid (PFDA) increases oxidative stress through inhibition of mitochondrial β-oxidation - Widhalm, Raimund; Granitzer, Sebastian; Natha, Benjamin; Zoboli, Ottavia; Derx, Julia; Zeisler, Harald; Salzer, Hans; Weiss, Stefan; Schmitner, Nicole; Kimmel, Robin A.; Österreicher, Tamina; Oberle, Raimund; et al. (Environmental pollution (1987), 2025)
Per- and polyfluoroalkyl substances (PFAS) are a large group of synthetic organic chemicals that are ubiquitous environmental pollutants. Among PFAS, perfluorodecanoic acid (PFDA) is one of the most toxic compounds, but the molecular basis behind its toxicity is not fully understood. In an interspecies comparison with placental cells (HTR-8/SVneo) and zebrafish embryos, we demonstrate that PFDA induces mitochondrial dysfunction and impairs fatty acid β-oxidation. Reduced β-oxidation leads to less TCA cycle activity, resulting in less NADH and consequently NADPH production. Thereby NADPH-dependent glutathione recycling is impaired, increasing cellular oxidative stress that can only be partially compensated by NRF2 activation. [Display omitted] •PFDA increases NRF2 activity in placental cells and zebrafish embryos.•PFDA inhibits mitochondrial β-oxidation.•PFDA treatment leads to reduced GSH recycling.